Loan and Advance Management of Nepal Bank Limited and Rastriya Banijya Bank - Bhandari, Hari Bahadur (Janapriya Journal of Interdisciplinary Studies, 2022)
The main objective of this study was to assess and compare loan and advance management of Nepal Bank Limited and Rastriya Banijya Bank. The study used descriptive and analytical research design. Two banks out of total 27 commercial banks in Nepal were selected based on judgmental sampling. Quantitative data are collected from secondary sources of annual audited report. The collected data were classified, coded and analyzed with the help of statistical tools like percentage, mean, standard deviation, coefficient of correlation, and coefficient of determination using MS-Word, MS-Excel, and Statistical Package for Social Science. Both the banks utilized most of the deposits in the forms of loan and advance. NBL has provided more amount for loan loss provision in comparison with the RBB. Non-performing loan to total loan and advance ratio showed that NBL (2.25%) has good management than the RBB (4.03%). Unlike this, the mean ratio of loan and advance to total assets ratio of NBL (55.7%) is lower than the RBB (61.48%) proved that RBB mobilized fund properly. Lower standard deviation and coefficient of variation of RBB have been indicated that the bank has more uniformity than the NBL except interest income to loan and advance ratio. The study showed that there is significant relationship of loan and advance with total deposit, loan loss provision, nonperforming loan and total assets of both banks except the non-performing loan and loan and advance of RBB.